Financial forecast: fast methods of estimation of working capital structural - Case comercial enterprise - Porlles Loarte, José (2013)
The growth of the country’s economy and therefore the market in all business activities is enabling the aggressive expansion of its sales. But this growth requires incremental liquidity as working capital. The business run the risk of limiting their growth if the liquidity needed to secure it exceeds the own generation of funds. Therefore require financial forecasts that they can visualize the incremental funds requirements well in advance, and know if they have with their own funds generated internally or manage what is necessary in the banking. In this article presents the methodology and interpretation of results in the use of two models for a quick estimate of the needs of funds, namely, the fund additional maneuver structural to sustain the increase in sales.